Sustainabilit y in traditional crops and in hydroponic culture of lettuce - Ruiz, Alexandra Souza; Souza, Sulma Vanessa; Sabbag, Omar Jorge [UNESP] (Centro Universitario de Maringa, 2019)
The sustainability of two production units of lettuce, the traditional and the hydroponic culture, in Dourados MS Brazil, is analyzed. Sustainability was evaluated by the System of Social Impact of Agro-livestock Activities (APOIA-SOCIAL), with a set of electronic sheets, integrated by 16 indexes of contribution from a specific agro-livestock activity. Four essential evaluation aspects were taken into account: i) employment, ii) economy, iii) health and iv) management and administration. The Qualitative, descriptive and exploratory method was employed. It was based on data from the 2006 Agro-Livestock Census by the Brazilian Institute of Geography and Statistics, and on bibliographic review. Hydroponic horticulture was highlighted with a 0.73 sustainability index. This rate was above the base line of indicators (=0.70). In spite of satisfactory performance, some indicators had low use rates and may jeopardize the sustainability of activities within the family production units.
Sustentabilidade em cultivos tradicional e hidropônico de alface
Keywords: Hydroponic crops; Lactuca sativa L.; Sustainability; Traditional